Anti-cancer activity and apoptosis inducing effect of methanolic extract of Cordia dichotoma against human cancer cell line - Rahman, Md. Azizur; Hussain, Arshad (Bangladesh Journal of Pharmacology, 2015)
MTT assay and DAPI staining test were performed to evaluate anticancer potential and to assess apoptosis inducing effect of methanolic extract of Cordia dichotoma leaves (MECD) against human cervical cancer cell line (HeLa). Changes in MMP and intracellular ROS level were also assessed by JC-1 and DCFH-DA staining. Total phenolic contents were determined by colorimetric principle. Levels of statistical significance were determined by one-way analysis of variance followed by Dunnetts posttest. Results showed that MECD with obtained IC50 of 202 µg/mL inhibited in vitro proliferation of human cervical cancer cells and induced apoptosis indicating its promising anticancer activity as compared to the standard tamoxifen with obtained IC50 of 48 µg/mL. Total phenolic contents was found to be 176.5 mg GAE/g dried extract. It was concluded that MECD possess promising anticancer activity and induce apoptosis.